Resonance in positron-helium scattering at medium energy - Chaudhuri, P.; Adhikari, S. K.; Ghosh, A. S. (Iop Publishing Ltd, 1997)
A narrow S-wave resonance has been found in the positron-helium system at about 30 eV, using the close-coupling approach, in excitation and rearrangement cross sections to He(1s2s), He(1s2p), Ps(1s) and Ps(2s) states by employing different combinations of the following basis functions: He(1s1s), He(1s2s), He(1s2p), Ps(1s) and Ps(2s), where Ps stands for the positronium atom.